A "lagoa azul" como espaço educativo não formal para alfabetização ecológica de estudantes das séries iniciais no município de Parintins - Silva, Glauciane Sousa da (2017)
Non-formal spaces present possibilities for teaching science, as well as developing ecological literacy with the aim of re-educating citizens in a new conception of life sustainability, motivated by experience and participation. The purpose of this research was to analyze how the ecological literacy process takes place in educational spaces with students from the initial grades of Elementary Education using the Natural Sciences proposal and the Social Representation of the "Blue Lagoon" of Parintins-AM. Comprehensiveness of the social context, school and space of the "Blue Lagoon", we opted for the mixed method in order to obtain a better understanding of the problem researched. Composed as subjects of the research 37 students, 01 teacher, 04 residents. And in the Social Representation we applied the technique (ALP) and participated 31 students, 13 teachers and 25 community members. The research reinforces the need to value partnerships between non-formal and formal spaces and to increase participation among school, students, community and others who are willing to collaborate with social projects in the preservation of natural environments. In the didactic sequence and proposed actions, it was observed that ecological literacy is possible, provided that pedagogical alternatives are sought anchored to the social reality of the subjects, in a way that can reflect ecological postures and sustainability standards, so that in the near future other Can enjoy the same possibilities as today. The experience allows a wealth of scientific knowledge, which makes the contents of Natural Sciences more stimulating and pleasant in the act of learning, as well as to develop emotional bonds, which awaken the formation of ecological consciousness. In this way it is possible to consider that the "Blue Lagoon" is an environment conducive to the Teaching of Sciences, with elements for the formation of the ecological subject. As a product, we present a proposal of pedagogical work to be explored under different aspects and that will be helping in an interdisciplinary way in teaching